Leadership, work performance and quality of care in intensive care units - Rios Alva, Guillermo Segundo (2025)
The objective of this study was to determine the levels achieved in the influence of leadership and work performance on the quality of care in the intensive care unit. The research was applied with a non-experimental, correlational, causal, cross-sectional design and three questionnaires were used: leadership, work performance and quality of care. The sample consisted of 11 physicians and 43 patients. The results showed a high level of leadership with 83.3%, the highest level of performance was high with 79.6% and the quality of care was also high with 75.9%. However, the Gamma test confirmed that leadership and work performance do not influence the quality of care, that, on the other hand, the quality of care is related to structural and organizational factors of the hospital environment. These findings invite us to rethink management strategies to optimize care in critical units.